Urban Settlement Development Based on Land Suitability in Sirimau District, Ambon City - Lasaiba, Chica Felisia; Salakory, Melianus; Lasaiba, Mohammad Amin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Urban settlement development is an essential issue that the government and society must consider. This study aims to determine urban settlement development based on land suitability levels. The study was conducted in Sirimau District using a survey method, with variables such as slope, inundation, erosion, mass movement, soil texture, and rock exposure. The analysis and evaluation process was conducted qualitatively by spatial analysis of the overlapping results of all land parameters. The study results show 15 land units in the Sirimau District, with four land classes suitable for settlements. The categories of land suitability are very suitable covering an area of 3181.34 ha (8.04%), suitable covering an area of 567.98 ha (1.51%), moderately suitable covering an area of 2852.05 ha (7.57%), and less suitable covering an area of 23592.48 ha (62.55%). The factors that hinder the development of settlements in the research area are steep slopes and the high risk of mass movement. Therefore, the priority for urban settlement development in Sirimau District is focused on the categories of land suitability that are very.